Analisis dan Evaluasi Desain Web Profil Sekolah dengan Pendekatan Nielsen Usability Model - Sirojul Munir; Mochamad Wisnu Nugroho (Jurnal Informatika Terpadu, 2022)
Harapan Bangsa Vocational School is a private vocational high school that currently uses information technology in the form of a school website to support teaching and learning activities. There is a problem on the school's website that it is not optimal in terms of access to the level of convenience by students. This study will redesign the school website by applying material design and the approach to aspects of the Usability Nielsen's Model. The website has easy access from aspects of learnability, efficiency, memorability, errors, and satisfaction. The final result of the website redesign of the Harapan Bangsa Vocational School using a Likert scale of 5, the average usability value was 4.03, which means that the website's appearance has been good in applying the five categories of usability the Nielsen Model.